THE PROGRAM OF LOCAL AND ECONOMIC DEVELOPMENT AND FUNCTIONAL LITERACY - Fukrotutsauroh, Aas (QARDHUL HASAN: MEDIA PENGABDIAN KEPADA MASYARAKAT, 2015)
Kuliah Kerja Nyata (KKN) is one of the manifestation of Tri Dharma of the University. It is an effort to improve the index of community development through the creation work ini the real situation. KKN would be expected as a facilitator of the social and economic problem, by optimizing the natural and human resources. The participant of a local economic thematic Djuanda University involved the villagers of Desa Pasir Angin to explore the local potention of the processing mushroom agriculture products and complete illiteracy complication through the literacy functional learning groups. Thematic KKN conducted all together by the university and West Java Government is expected could increase IPM, economic components, and the power of people purchasing, thus fulfill all the components, develop of the potential all the local economic potention as a meaningfull contribution. Despite of completing the illiteracy problem this program, also serve the ability to utilize the skill of illiteracy to build the confidence and the development of logical reasoning practical, intern, able to develop their potential to meet the livelihood.